PENGARUH YURISPRUDENSI TERHADAP PRINSIP KEMERDEKAAN HAKIM - Sianipar, Favian Partogi Alexander (TANJUNGPURA LAW JOURNAL, 2020)
In the legal system in Indonesia, a jurisprudence is often used in the context of legal discovery. Although theoretically, the Judge is not bound by Jurisprudence, on the other hand, it creates a firm intention for Judges to follow higher court decisions. This raises a contradiction regarding the position of Jurisprudence in the legal system adopted in Indonesia. The contradiction came from legal scholars in particular Judges who did not approve of the use of Jurisprudence in their decisions because it violated the independence of Judges who had been regulated in Article 24 of the 1945 Constitution of the Republic of Indonesia and guidelines for the enforcement of a code of ethics and a code of conduct for judges. Based on the discussion above, in this article, the writer is interested in exploring whether the application of jurisprudence can affect the independence of judges. This article concludes that when the Supreme Court judges a court decision with a permanent legal force as a jurisprudence, it is changed into positive law. Then other judges can use jurisprudence as a basis for consideration in their decisions. This certainly does not damage the independence of the Judges listed in the code of ethics in deciding a case.Dalam sistem Hukum di Indonesia masih sering digunakan suatu Yurisprudensi dalam rangka penemuan hukum. Sekalipun secara teoritis memang Hakim tidak terikat dengan Yurisprudensi namun disisi lain menciptakan intensi yang kuat bagi para Hakim untuk mengikuti putusan-putusan pengadilan yang lebih tinggi. Hal ini menimbulkan suatu pertentangan mengenai kedudukanYurisprudensi dalam sistem hukum yang dianut di Indonesia. Pertentangan tersebut berasal dari sarjana hukum pada khususnya Hakim yang tidak menyetujui digunakan Yurisprudensi dalam putusannya karena melanggar suatu kemandirian Hakim yang telah diatur dalam Pasal 24 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 serta panduan penegakan kode etik dan pedoman perilaku Hakim. Bertitik tolak dari pembahasan tersebut di atas, dalam artikel ini penulis tertarik untuk menggali apakah berlakunya yurisprudensi dapat mempengaruhi kemerdekaan hakim. Artikel ini menyimpulkan bahwa Ketika Suatu putusan Pengadilan yang berkekuatan hukum tetap tersebut di nilai oleh Mahkamah Agung sebagai sebuah Yurisprudensi, maka sifatnya berubah menjadi hukum positif. Maka Hakim lain dapat mempergunakan yurisprudensi tersebut sebagai dasar pertimbangan dalam putusannya. Hal tersebut tentu tidak menciderai kemandirian Hakim yang tercantum dalam kode etik dalam memutuskan suatu perkara.